Selective prevention of mechanical hyperalgesia after incision by spinal ERK1/2 inhibition. (26th June 2014) - van den Heuvel, I.; Reichl, S.; Segelcke, D.; Zahn, P.K.; Pogatzki‐Zahn, E.M.
Abstract Background Activation of extracellular signal‐regulated kinases (ERK1/2) has been shown to play an important role in several pain states. Here we investigated the ERK1/2 contribution to non‐evoked and evoked pain‐like behaviour in rats after surgical incision. Methods Spinal phosphorylation of ERK1 and ERK2 was assessed 15 min, 4 h, 24 h and 5 days after plantar incision and sham incision. The effect of PD98059, a specific inhibitor of ERK1/2 activation, administered intrathecally (IT) 1 h before or 2 h after incision on spinal ERK1 and ERK2 phosphorylation was assessed. In behavioural experiments, the effect of PD98059 administered 1 h before or after incision on non‐evoked pain behaviour and mechanical and heat hyperalgesia was assessed. Results Phosphorylated ERK1 and ERK2 were rapidly increased in the ipsilateral dorsal horn from rats after incision post‐operatively. This increased ERK1 and ERK2 phosphorylation were blocked by PD98059 administered before incision. In congruence, IT administration of PD98059 before incision delayed mechanical hyperalgesia after incision; however, administration after incision had only a modest effect on mechanical hyperalgesia. In addition, PD98059 did not affect non‐evoked pain behaviour or heat hyperalgesia after incision. Conclusion The results suggest that spinal ERK1 and ERK2 are involved in regulation of pain after incision differentially with regard to the pain modality. Furthermore, blockade of ERK1/2 activation was most effective in a preventive manner, a condition which is rare after incision. Spinal ERK1/2 inhibition could therefore be a very useful tool to manage selectively movement‐evoked pain after surgery in the future.